Ownership Structure, Media Visibility and Earnings Management: An Empirical Study in the Moroccan Context - LAKSSOUMI , Fatima (Revue du contrôle, de la comptabilité et de l’audit, 2024)
The purpose of this paper is to shed light on the effect of ownership structure on earnings management practices in a unique setting: Morocco, where 1) ownership structure is characterized by the presence of a controlling shareholder (often a family), and 2) corporate governance standards and investors’ legal system protection are poorly implemented. This study also extends previous research by investigating the moderating effect of media coverage on the relationship between ownership structure and earnings management. Based on a panel of data from 38 Moroccan listed companies between 2010 and 2018, we use the fixed effect regression model, estimated with robust errors and clustered at the firm levels, to test our research hypotheses. Results show that firms with concentrated ownership are more likely to expropriate minority interests by managing earnings. The linear moderating effect of the number of media items covered about the company on the association between capital concentration, family control and earnings management is not significant. However, we find that media exposure has a significant inverted-U shape moderating effect on the relationship between family control and earnings management.